Shags in Antarctica: their feeding behaviour and ecological role in the marine food web - Casaux, Ricardo Jorge (2006)
Feeding behaviour, ecological role in the marine food web and population trends of the Antarctic shag Phalacrocorax bransfieldensis and the South Georgia shag P. georgianus in Antarctica are analysed. The diving depths and duration recorded for these shags are the deepest and longest among all flying birds in Antarctica and match deep dives performed by small Antarctic penguins. Individual shags of both sexes partition foraging depths and food resources, which might diminish intra-specific competition. Like other sub-Antarctic shags, P. bransfieldensis and P. georgianus are bottom feeders that prey predominantly on demersal fish. In the southern Scotia Arc and west Antarctic Peninsula, nototheniids, mainly Notothenia coriiceps, constitute their main prey. Shag partners alternate the time at sea and, as the energy requirements at the nest increase, they increase the number but reduce the duration of the feeding trips. A steady declining trend in the number of breeding pairs of both species has been observed in the last decade at several Antarctic localities; this phenomenon at the South Shetland Islands might be at least partially explained by the effect of the commercial fishery on their prey. In inshore shallow waters shags occupy the trophic niche of main predators of demersal fish and play an important ecological role as regulators of populations of particular fish prey that have marked site fidelity. The potential use of shags as biomonitors in Antarctica is discussed. Key Words: Antarctic shag; diving; foraging patterns; monitoring; notothenioids; South Georgia shag.